2017
DOI: 10.1371/journal.pone.0181839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium electroporation in combination with metformin in vivo and correlation between viability and intracellular ATP level after calcium electroporation in vitro

Abstract: BackgroundCalcium electroporation is a new experimental anti-cancer treatment where calcium is internalized into cells by application of short, high voltage pulses. Calcium electroporation has been shown to induce tumor necrosis associated with ATP depletion while the effect on normal fibroblasts was limited when investigated in a 3D in vitro spheroid model. We aimed to investigate the effect of calcium electroporation in combination with metformin, a drug that affects intracellular ATP level. We also aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…Similar effects can be reached with calcium electroporation as with electrochemotherapy using bleomycin, but no synergistic effect is seen when combining calcium and bleomycin before electroporation [84]. There was no effect of treatment with calcium alone in concentrations up to 5 mM [18,77,[80][81][82] and even up to 20 mM in the two cell lines where such high concentrations were tested [78]. This is unlike treatment with bleomycin alone where some effect is seen; however, this effect is much less than when combined with electroporation [81,84].…”
Section: Effect On Cancer Cells In Vitro and In Vivomentioning
confidence: 70%
See 2 more Smart Citations
“…Similar effects can be reached with calcium electroporation as with electrochemotherapy using bleomycin, but no synergistic effect is seen when combining calcium and bleomycin before electroporation [84]. There was no effect of treatment with calcium alone in concentrations up to 5 mM [18,77,[80][81][82] and even up to 20 mM in the two cell lines where such high concentrations were tested [78]. This is unlike treatment with bleomycin alone where some effect is seen; however, this effect is much less than when combined with electroporation [81,84].…”
Section: Effect On Cancer Cells In Vitro and In Vivomentioning
confidence: 70%
“…There seems to be a similar effect of calcium electroporation when treating with calcium concentrations between 100-500 mM (injected in a volume equivalent to 50% of the tumor volume) and with injection volumes from 20% to 80% of the tumor volume (with 168 mM CaCl 2 ) [61]. The calcium concentrations used in vivo [18,61] are much higher than the concentrations inducing cell death in vitro [77,80], which is also seen when using bleomycin in combination with electroporation [79,84]. This is likely due to the smaller extracellular volume (ECV) in tissue compared with cells in suspension in vitro, which is also supported by a study on spheroids, a 3D in vitro model [85], where the drug concentrations (calcium or bleomycin) were similar to the in vivo studies and the ECV of spheroids is comparable to the ECV of tissue.…”
Section: Effect On Cancer Cells In Vitro and In Vivomentioning
confidence: 94%
See 1 more Smart Citation
“…Ca-EP is a novel anticancer treatment that has been used successfully with tumours exhibiting various histologies. Preclinical studies provided the first support for the efficacy across cancer histologies, as well as an explanation of the mechanisms of action [11,13,14,[20][21][22][23][24][25][26][27]. The results of the first clinical trials suggested that Ca-EP is safe and efficient at the local level for tumours of different types, including cutaneous metastases from breast cancer and malignant melanoma and recurrent head and neck cancer [11,20].…”
Section: Discussionmentioning
confidence: 99%
“…The 2 mM concentration was selected based on the available knowledge on calcium electroporation. It is known that a threshold in concentration exists when the calcium www.nature.com/scientificreports www.nature.com/scientificreports/ electrotransfer starts to be effective, while 2 mM is an optimal dose across many cell lines 20 . The resultant conductivity of the medium during the 2 mM Ca 2+ electroporation procedure was 0.08 S/m.…”
Section: Resultsmentioning
confidence: 99%